Peningkatan Keterampilan Academic Writing Dalam Mendukung Publikasi Ilmiah Bagi Anggota New Generation Club Makassar - Muhamad Yahrif; Suharti Sirajuddin; Basri Basri (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Academic writing skills are an important competency for the younger generation to support a culture of scientific publication and academic capacity development. However, based on initial observations of members of the Makassar New Generation Club (NGC), it was found that most participants still experienced difficulties in compiling scientific articles, using reputable references, applying APA 7-based citation techniques, and understanding scientific publication procedures. Therefore, this Community Service (PKM) activity aims to improve academic writing skills in supporting scientific publications for members of the Makassar New Generation Club. The PKM activity was carried out on March 9, 2026, using a hands-on training and mentoring method. The stages of the activity included material delivery, scientific article writing practice, training in using an academic reference search platform, discussion, mentoring, and evaluation. The results showed that this training was able to improve participants' understanding of the structure of scientific article writing, the use of credible academic references, paraphrasing techniques to avoid plagiarism, and the ability to use scientific writing support applications such as Google Scholar and Mendeley. In addition, participants also showed increased motivation, self-confidence, and interest in writing and publishing their scientific works. Thus, this PKM activity provides a positive contribution in building a culture of academic literacy and increasing scientific publication competence in the youth organization environment.